(untitled) (Research, Society and Development, 2022)
This article aims to reflect on the implication of telework performed by women in the context of the pandemic and its relationship with domestic life. To this do so, we present how the pandemic context boosted remote work and intended the boundaries between the public and the private. The methodology of the study was qualitative in nature, bibliographic basis and documentary data made available in the years 2020 and 2021 by Brazilian government agencies and by private and non-governmental organizations that published studies and research e sites of Internet. The results and discussions dialogue with the hierarchical duality of the male/female in domestic work and the reorganization of work activities in the context of the pandemic, producing an intense overload in the daily life of women. The final considerations point to the need for reflection on the changes produced by the pandemic with the acceleration of telework and the effects produced on the popular classes in the reproduction of social inequalities and especially of women’s lives.